VENTRICLE ASSIST DEVICE: PAST, PRESENT, AND FUTURE NONPULSATILE PUMPS - G. Р. Itkin (Вестник трансплантологии и искусственных органов)
The article briefly describes the history of the non-pulsating type blood pumps for ventricular assist circulation and heart-lung machine. Disclosed the main advantages of these pumps before pulsating type, especially for implantable systems development. However, disadvantages of these pumps and the directions of minimize or eliminate ones have shown. Specific examples of our implantable centrifugal and axial pump developments are presented. Declare the ways to further improve the pumps.